The effect of sowing date in establishing Camelina sativa as a valuable summer crop in France - Susana Silvestre; Anais Da Costa; Thomas I. David; Frédérique Tellier; Javier Prieto; Paloma Leon; Yuri Herreras Yambanis; Richard P. Haslam; Jean-Denis Faure (Field Crops Research, 2026)

A VNIR spectral database of terrestrial magmatic rocks for the interpretation of Martian plagioclase hyperspectral detections - M. Barthez; J. Flahaut; M. Guitreau; R. Pik; G. Ito; C. Delangle; J.-P. Gremilliet; B. Luais; F. Faure (Icarus, 2026)

A reappraisal of the amorphization kinetics of water ice: Combined experimental and numerical investigations and amorphization cross-sections in the 90–120 K range - A. Moingeon; E. Quirico; O. Poch; M. Faure; P. Boduch; A. Domaracka; H. Rothard; B. Schmitt; M. Toulemonde; J. Rangama; D. Bockelée-Morvan; T. Fouchet; et al. (Icarus, 2026)

A collaborative and low cost acquisition chain for collecting spatialized observations in agriculture - S. Moinard; B. Oger; G. Brunel; A. Ducanchez; T. Crestey; P. Faure; L. Pichon; B. Tisseyre (Computers and Electronics in Agriculture, 2025)

Multi-millennia slip rate relationships between closely spaced across-strike faults: Temporal earthquake clustering of the Skinos and Pisia Faults, Greece, from in situ 36Cl cosmogenic exposure dating - Sam Mitchell; Claudia Sgambato; Jenni Robertson; Gerald P. Roberts; Joanna P. Faure Walker; Zoë Mildon; Athanassios Ganas; Ioannis Papanikolaou; Francesco Iezzi; Joakim Beck; Steven A. Binnie; Tibor Dunai; et al. (Journal of Structural Geology, 2025)

The relationship between kinematics and fault geometry for surface coseismic ruptures on across-strike faults: New observations of slip vectors and displacements along the Pisia and Skinos faults from the 1981 Eastern Gulf of Corinth, Greece earthquakes - Sam Mitchell; Gerald P. Roberts; Joanna P. Faure Walker; Francesco Iezzi; Claudia Sgambato; Jennifer Robertson; Zoë K. Mildon; Athanassios Ganas; Ioannis D. Papanikolaou; Elias J. Rugen (Journal of Structural Geology, 2024)

A ring trial to harmonize Toxoplasma gondii microsatellite typing: comparative analysis of results and recommendations for optimization - M. Joeres; G. Cardron; K. Passebosc-Faure; N. Plault; M. Fernández-Escobar; C. M. Hamilton; L. O’Brien-Anderson; R. Calero-Bernal; L. Galal; C. Luttermann; P. Maksimov; F. J. Conraths; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)
A ring trial among five European laboratories was organized to reach consistency in microsatellite (MS) typing of the zoonotic parasite Toxoplasma gondii . Three sample sets were circulated and analyzed by each laboratory following a previously published method that is based on fragment length polymorphism of 15 MS markers. The first sample set compared typing results in general and focused on effects of DNA concentration; the second sample set focused on the polymorphic fingerprinting markers that can differentiate T. gondii strains within the same archetypal lineage; and the third set focused on non-archetypal genotypes. Methodological variations between laboratories, including the software programs used to determine MS fragment length, were collated using a questionnaire. Overall, lineage-level typing results reached a high level of agreement, especially in samples with the highest DNA concentrations. However, laboratory-specific differences were observed for particular markers. Major median differences in fragment length, of up to 6 base pairs, were related to the fluorophore used to label fragment-specific primers. In addition, primer pairs with identical sequences obtained from different suppliers resulted in fragments of differing length. Furthermore, differences in the way the sequencing profiles were assessed and interpreted may have led to deviating results in fragment length determination. Harmonization of MS typing, for example, by using the same fluorophores or by numerical adjustments applied to the fragment-lengths determined, could improve the uniformity of the results across laboratories. This is the first interlaboratory comparison, providing guidelines (added as a supplement) for the optimization of this technique.

On a radiolytic origin of red organics at the surface of the Arrokoth Trans-Neptunian Object - Eric Quirico; Aurore Bacmann; Cédric Wolters; Basile Augé; Laurène Flandinet; Thibault Launois; John F. Cooper; Véronique Vuitton; Thomas Gautier; Lora Jovanovic; Philippe Boduch; Hermann Rothard; et al. (Icarus, 2023)

Transport and Adsorption of Nano-Colloids in Porous Media Observed by Magnetic Resonance Imaging - A. P. Lehoux; P. Faure; E. Michel; D. Courtier-Murias; S. Rodts; P. Coussot (Transport in Porous Media, 2017)

Effect of thermal pre-treatment on the availability of PAHs for successive chemical oxidation in contaminated soils - M. Usman; A. Chaudhary; C. Biache; P. Faure; K. Hanna (Environmental Science and Pollution Research, 2016)

Phylogeography in continuous space: coupling species distribution models and circuit theory to assess the effect of contiguous migration at different climatic periods on genetic differentiation in B usseola fusca ( L epidoptera: N octuidae) - S. Dupas; B. le Ru; A. Branca; N. Faure; G. Gigot; P. Campagne; M. Sezonlin; R. Ndemah; G. Ong'amo; P.‐A. Calatayud; J.‐F. Silvain (Molecular Ecology, 2014)
Current population genetic models fail to cope with genetic differentiation for species with large, contiguous and heterogeneous distribution. We show that in such a case, genetic differentiation can be predicted at equilibrium by circuit theory, where conductance corresponds to abundance in species distribution models ( SDM s). Circuit‐ SDM approach was used for the phylogeographic study of the lepidopteran cereal stemborer B usseola fusca F üller ( N octuidae) across sub‐ S aharan A frica. Species abundance was surveyed across its distribution range. SDM s were optimized and selected by cross‐validation. Relationship between observed matrices of genetic differentiation between individuals, and between matrices of resistance distance was assessed through Mantel tests and redundancy discriminant analyses ( RDA s). A total of 628 individuals from 130 localities in 17 countries were genotyped at seven microsatellite loci. Six population clusters were found based on a B ayesian analysis. The eastern margin of D ahomey gap between E ast and W est A frica was the main factor of genetic differentiation. The SDM projections at present, last interglacial and last glacial maximum periods were used for the estimation of circuit resistance between locations of genotyped individuals. For all periods of time, when using either all individuals or only E ast A frican individuals, partial M antel r and RDA conditioning on geographic distance were found significant. Under future projections (year 2080), partial r and RDA significance were different. From this study, it is concluded that analytical solutions provided by circuit theory are useful for the evolutionary management of populations and for phylogeographic analysis when coalescence times are not accessible by approximate B ayesian simulations.

Treatment of hydrocarbon contamination under flow through conditions by using magnetite catalyzed chemical oxidation - M. Usman; P. Faure; C. Lorgeoux; C. Ruby; K. Hanna (Environmental Science and Pollution Research, 2013)

Speciation of Organic Matter and Heavy Metals in Urban Wastewaters from an Emerging Country - R. El Khatib; B. S. Lartiges; A. El Samrani; P. Faure; J. Houhou; J. Ghanbaja (Water, Air, & Soil Pollution, 2012)

Geochronological and geochemical characterization of magmatic-hydrothermal events within the Southern Variscan external domain (Cévennes area, France) - A. Chauvet; N. Volland-Tuduri; C. Lerouge; V. Bouchot; P. Monié; X. Charonnat; M. Faure (International Journal of Earth Sciences, 2012)

Field observations from the Aquila, Italy earthquake of April 6, 2009 - T. Rossetto; N. Peiris; J. E. Alarcon; E. So; S. Sargeant; M. Free; V. Sword-Daniels; D. Del Re; C. Libberton; E. Verrucci; P. Sammonds; J. Faure Walker (Bulletin of Earthquake Engineering, 2011)

Land use monitoring by remote sensing in tropical forest areas in support of the Kyoto Protocol: the case of French Guiana - N. Stach; A. Salvado; M. Petit; J. F. Faure; L. Durieux; C. Corbane; P. Joubert; D. Lasselin; M. Deshayes (International Journal of Remote Sensing, 2009)

Incidence of kyphosis deformities in natural population of Atherina lagunae (Trabelsi et al. 2002) from the Tunis North Lake, Tunisia - N. Ayed; E. Faure; J.-P. Quignard; F. Maamouri; M. Trabelsi (Marine Biology, 2008)

Root-knot nematode (Meloidogyne spp.) Me resistance genes in pepper (Capsicum annuum L.) are clustered on the P9 chromosome - C. Djian-Caporalino; A. Fazari; M. J. Arguel; T. Vernie; C. VandeCasteele; I. Faure; G. Brunoud; L. Pijarowski; A. Palloix; V. Lefebvre; P. Abad (Theoretical and Applied Genetics, 2007)

High dietary sucrose triggers hyperinsulinemia, increases myocardial β-oxidation, reduces glycolytic flux and delays post-ischemic contractile recovery - D. Gonsolin; K. Couturier; B. Garait; S. Rondel; V. Novel-Chaté; S. Peltier; P. Faure; P. Gachon; Y. Boirie; C. Keriel; R. Favier; S. Pepe; et al. (Molecular and Cellular Biochemistry, 2007)

Phylogeography and population genetics of the maize stalk borer Busseola fusca (Lepidoptera, Noctuidae) in sub‐Saharan Africa - M. SEZONLIN; S. DUPAS; B. LE RÜ; P. LE GALL; P. MOYAL; P.‐A. CALATAYUD; I. GIFFARD; N. FAURE; J.‐F. SILVAIN (Molecular Ecology, 2006)
The population genetics and phylogeography of African phytophagous insects have received little attention. Some, such as the maize stalk borer Busseola fusca , display significant geographic differences in ecological preferences that may be congruent with patterns of molecular variation. To test this, we collected 307 individuals of this species from maize and cultivated sorghum at 52 localities in West, Central and East Africa during the growing season. For all collected individuals, we sequenced a fragment of the mitochondrial cytochrome b . We tested hypotheses concerning the history and demographic structure of this species. Phylogenetic analyses and nested clade phylogeographic analyses (NCPA) separated the populations into three mitochondrial clades, one from West Africa, and two — Kenya I and Kenya II — from East and Central Africa. The similar nucleotide divergence between clades and nucleotide diversity within clades suggest that they became isolated at about the same time in three different refuges in sub‐Saharan Africa and have similar demographic histories. The results of mismatch distribution analyses were consistent with the demographic expansion of these clades. Analysis of molecular variance ( amova ) indicated a high level of geographic differentiation at different hierarchical levels. NCPA suggested that the observed distribution of haplotypes at several hierarchical levels within the three major clades is best accounted for by restricted gene flow with isolation by distance. The domestication of sorghum and the introduction of maize in Africa had no visible effect on the geographic patterns observed in the B . fusca mitochondrial genome.

Identification of type I resistance to Fusarium head blight controlled by a major gene located on chromosome 4A of Triticum macha - A. Steed; E. Chandler; M. Thomsett; N. Gosman; S. Faure; P. Nicholson (Theoretical and Applied Genetics, 2005)

Effect of Wetting on the Dynamics of Drainage in Porous Media - N. Shahidzadeh-Bonn; A. Tournié; S. Bichon; P. Vié; S. Rodts; P. Faure; F. Bertrand; A. Azouni (Transport in Porous Media, 2004)

Screening of segregating cocoa genotypes for resistance to vascular-streak dieback under natural conditions in Papua New Guinea - Y. Efron; J. Marfu; M. Faure; P. Epaina (Australasian Plant Pathology, 2002)

The sounds of silence: cessation of singing and song pausing are ultrasound-induced acoustic startle behaviors in the katydid Neoconocephalus ensiger (Orthoptera; Tettigoniidae) - P. A. Faure; R. R. Hoy (Journal of Comparative Physiology A, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Pharmacokinetics of intravenous methylprednisolone and oral prednisone in paediatric patients with inflammatory bowel disease during the acute phase and in remission - C. Faure; J. André; C. Pelatan; A. Munck; M. Giraud; J. P. Cèzard; E. Jacqz-Aigrain (European Journal of Clinical Pharmacology, 1998)

Interrelationships of the two families constituting the Lophogastrida (Crustacea: Mysidacea) inferred from morphological and molecular data - J.-P. Casanova; L. De Jong; E. Faure (Marine Biology, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Relationships between coral reef substrata and fish - P. Chabanet; H. Ralambondrainy; M. Amanieu; G. Faure; R. Galzin (Coral Reefs, 1997)